Antibiofilm activity of Gayo Arabica coffee (Coffea arabica L.) bean ethanolic extract against Pseudomonas aeruginosa and Candida albicans: in vitro and in silico studies - Raisha Fathima; Rima Ristianti; Rizkiyah Rizkiyah; Zulfitri Zulfitri; Tristia Rinanda (Faculty of Mathematics and Natural Science (FMIPA), Universitas Syiah Kuala, 2026)
Microbes form infectious biofilms to avoid antibiotic mechanisms, leading to the rise of antibiotic resistance. This phenomenon demands massive development of novel antibiofilm agents. Coffee plants have been investigated as antibiofilm agents despite their value as a popular export commodity. Gayo Arabica coffee, a signature product of Aceh, represents a sustainable and locally abundant natural resource. The aim of this study was to determine the antibiofilm activity of Gayo Arabica coffee bean extract against two of the most well-known biofilm producers, namely Pseudomonas aeruginosa and Candida albicans. The minimum inhibitory concentrations of the 96% ethanol-macerated coffee beans were identified against both microbes. The antibiofilm activity was evaluated based on inhibition and degradation assays. Chemical profiling of the extract was performed using Gas Chromatography-Mass Spectrometry, followed by molecular docking to assess interactions between compounds and biofilm-associated proteins in P. aeruginosa and C. albicans. The extract demonstrated antibiofilm activities against both microbes, which may be associated with the dominant compounds, particularly caffeine, hexadecanoic acid, and cis-13,16-docosadienoic acid. Caffeine had the strongest binding affinity to target proteins based on the docking analysis. This study exhibits the potent antibiofilm activity of Gayo Arabica coffee bean extract against P. aeruginosa and C. albicans. Keywords: biofilm, resistance, Pseudomonas aeruginosa, Candida albicans, Gayo coffee